Librarian’s Stereotypes and Social Role in the cinematographic discourse - Iturbe Fuentes, Luis; Ramítez Leyva, Elsa M. (Revista General de Información y Documentación, 2014)
Reel librarians representation is an issue that has awakened the interest of librarianship field because it provides different elements for leadership and direction studies, librarianship education, librarian’s social function, and gender studies, among others. This paper shows two views upon reel librarians representation: the first one is related to physical stereotypes and their psychological attitude; the other one is about librarians social role, values, virtues, gender issues, and humorous situations that they play, as well as symbolic elements which prevail through the social imagery. Each of these characteristics was identified throughout the analysis of different films.